Legal grounds natural resources, identity, and the law in Jharkhand - Sundar, Nandini (New Delhi Oxford University Press, 2009)
Contributed articles.
Includes bibliographical references (p. [229]-246) and index.
Keywords: Conservation of natural resources -- Law and legislation -- India -- Jharkhand; Identity politics; Culture and law